Efeitos fotobiomoduladores do diodo emissor de luz azul na cicatrização de queimaduras cutâneas - Fernandes Neto, José de Alencar (2021)
Burns are considered a worldwide public health issue. Depending on the depth, they can destroy all layers of the skin and affect muscles, ligaments, tendons, and bones. Photobiomodulation therapy with the use of Light Emitting Diode (LED) of different wavelengths, including blue LED, is currently being studied as a treatment that aims to optimize the wound healing process. Therefore, the aim of this study was to evaluate the photobiomodulatory effects of blue LED during the healing process of cutaneous burns, through clinical and histological parameters. Preclinical in vivo research was carried out with a quantitative analytical approach. Sample was composed for 50 Wistar rats divided into two groups: control (CTRL) (n=25) and blue LED (LED) (n=25). Also, subgroups of five animals for each time of euthanasia (7, 14, 21, 28 and 32 days) were made. After burn induction, therapy was performed daily with blue LED light (470nm, 1W, 0.44 W/cm2, 12.5 J/cm2, and 28 seconds per point) in contact with four points of the wound (total: 50 J/cm2). For the CTRL group, there was just the simulation of the treatment. Clinical evaluations were performed and the Wound Retraction Index (WRI) was calculated. Histological sections were stained with Hematoxylin-Eosin and toluidine blue for analysis of re-epithelialization, inflammatory infiltrate, and mast cells. Immunohistochemical analyzes were performed using the monoclonal anti-α-SMA antibody, for quantification of myofibroblasts, and the monoclonal anti-TGF-β1 (transforming growth factor β1) antibody. Data from clinical evaluations were descriptively analyzed. The median numbers of the other data were analyzed using the Mann-Whitney test. A significance level of 5% (p<0.05) was considered. At 7 days, bleeding background was observed in 3 cases (60%) in the CTRL. There were no statistically significant differences in WRI between groups (p>0.05). In LED, there was greater re-epithelialization at 7 and 14 days (p<0.05), greater amount of inflammatory cells at 7 days (p=0.015), higher concentration of mast cells at 21 and 32 days (p<0.05), and a smaller amount of myofibroblasts at 14, 21, 28, and 32 days (p<0.05), when compared to CTRL. In the epithelium, the percentage of TGF-β1 positive cells was higher in the LED group at 21, 28 and 32 days (p<0.05), and lower in the connective tissue at all experimental times, with statistically significant differences to 7, 14 and 21 days (p<0.05). In conclusion, according to the protocol established, the results suggest that depending on the period, the blue LED can modulate the healing processes of third-degree skin burns. The light is able to stimulate re-epithelialization and inflammatory response in early stages. Also, it can induce a higher concentration of mast cells in the evaluated times. Furthermore, the light seems to inhibit myofibroblast differentiation and TGF-β1 expression in connective tissue and induce the expression of this cytokine in epithelial tissue in more advanced stages of healing. Despite this, this therapy does not appear to have significant effects on the retraction of third-degree burns. Future studies are important to deepen the knowledge about the effects of this type of light on the healing of wounds.